PENGARUH KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN: Studi Kasus Pada PT. Fiskaria Jaya Suara Surabaya - Ratih Tristianingsih; Achmad Daengs GS; Ramansyah Hidayat (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
This study aims to determine: (1) The effect of job satisfaction and work environment on the performance of employees of PT. Fiscaria Jaya Suara Surabaya simultaneously, (2) The effect of job satisfaction and work environment on the performance of employees of PT. Fiscaria Jaya Suara Surabaya partially, (3) The influence of job satisfaction and work environment on these variables which have a dominant effect on the performance of employees of PT. Fiscari Jaya Suara Surabaya. This research is a research using a quantitative approach. The subjects of this study were employees of PT. Fiscari Jaya Suara Surabaya. The sample collection used a census sample of 40 people, but only 34 respondents were obtained in this study. The data collection method used interviews before the thesis and in the research process by distributing questionnaires in the form of questionnaires and google forms. Data analysis was carried out in this study using multiple linear regression analysis and multiple determination coefficient analysis. From the results of the analysis using SPSS (Statistical Package for the Social Sciences) shows that job satisfaction and work environment on employee performance have a significant effect simultaneously or partially. And the dominant independent variable on employee performance at PT. Fiscaria Jaya Suara Surabaya is the independent variable of the work environment.